Developing low carbon port potential: Cost benefit & carbon footprint analyses - Malte Jahn; Jan Wedemeier (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2018)
Cost benefit analysis (CBA) is a systematic approach to compare the costs and bene-fits of alternatives, e.g. a decision between the construction or non-construction of a traffic light, in order to assess the welfare change. The purpose of a CBA is to facilitate a more efficient allocation of resources, mainly in terms of investments decisions. In order to assess the performance of the low carbon port development investments funded within the DUAL ports project, CBA can be applied.
Keywords: 330